Entre fios, tramas e urdumes: tecendo compreensões sobre a formação inicial de professores com identidade cultural digital na Amazônia Oeste Paraense - MELO, Narelly Tavares Rodrigues e (Universidade Federal do Oeste do Pará, 2024)
The research presents the investigation about the initial training of teachers with digital cultural identity in the western Pará State, Brazilian Amazon, being this a bibliographical, documental and field study. The theoretical assumptions include discussions about culture and cultural identity, with emphasis on the contributions of authors of Cultural Studies; as well as the problematization of the term “digital natives”, coined by Marc Prensky (2001), which has been popularized in recent years as a reference to the subjects born in the digital era, demarcating the generations in “natives” and “digital immigrants”. In counterpoint, in Stuart Hall's contributions (2006), we reflect on the digital culture, the dislocations of postmodern subjects, the emergence of new cultural identities and the conception of a digital cultural identity. We also present theoretical discussions about the formation and professor profession, focusing on teacher education in Brazil and the process of building teacher identity in initial training, highlighting the higher education and the teaching and learning process of our graduate generations. We situate these discussions in the Amazonian realities, recognizing that we start from opposite identity phenomena, since the digital cultural identity presents itself as a new identity and the Amazonian identity presents itself as a local identity. The methodological assumptions were: documentary research, investigating the institutional and pedagogical documents of the Federal University of Western Pará (Portuguese: Universidade Federal do Oeste do Pará - UFOPA) and its Degree in Educational Informatics (Portuguese: Licenciatura em Informática Educacional – LIE); and field research using the techniques of participant observation, application of questionnaires and interviews adapted to the reality of non face-to-face pedagogical activities or remote activities of UFOPA, due to the pandemic of COVID-19. Documentary Analysis and Content Analysis were the methods used in the treatment of the data. We weave understandings about the digital culture in Ufopa and in the LIE/Ufopa and point to specific situations of the very process of identity construction of the Course and the teacher education process, highlighting the perceptions of the research participants about the teaching methodologies, the evaluation and classroom routines, as well as the relationships of teachers with the new information and communication technologies (NICTs) in teaching practice from the context of emergency remote classes, and the relationships between professors and students in the formative process. We recognize that initial training produces teachers with a digital cultural identity when it is configured, from its pedagogical proposal to the teaching practice, in the valorization of the digital culture of the postmodern subject. The conclusions converge to the necessary understanding and discussion of the phenomena of digital culture and digital cultural identity, and Ufopa, as a young university in the interior of the western Pará State, presents continuity in its process of institutional maturation that, with the support of the LIE, has disruptive potential to include and broaden the debates on digital culture in the training of Amazonian professors.